Gambaran Tingkat Pengetahuan Kader Tentang Manfaat Posyandu Pada Ibu Hamil - Ummi Irmadani Harahap; Evi Erianty Hasibuan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Cadres are human figures who attract public attention, the percentage of active cadres nationally is 69.2%, so the drop out rate for cadres is around 30.8%. The benefits of posyandu for pregnant women are that pregnant women will be monitored for their weight, receive 1 tablet of added blood every day, pregnant women check themselves regularly and want to give birth assisted by health workers, pregnant women and fertile women (WUS) receive Tetanus Toxoid (TT) immunization . The purpose of this study was to find out how the level of knowledge of cadres about the benefits of posyandu for pregnant women in the Padangmatinggi Public Health Center, Padangsidimpuan City in 2013. This type of research was quantitative with a descriptive design using a questionnaire. The population in this study were 110 cadres in the Padangmatinggi Public Health Center with a total sample of 22 people, the sampling method was systematic random sampling. The results of the study based on knowledge the majority had sufficient knowledge of 11 people (50%), based on the age of the majority aged 25-35 years as many as 17 people (77,27%), based on education the majority had high school education as many as 17 people (77,27%), based on occupation the majority of housewives as many as 14 people (63.63%), based on the majority of information sources from Electronic Media as many as 9 people (40.90%). Based on the discussion, the conclusions drawn from the study are a description of the level of knowledge of cadres about the benefits of posyandu for pregnant women influenced by age, education, occupation, and sources of information and the conclusion that the level of knowledge of cadres about the benefits of Posyandu for pregnant women is still quite knowledgeable. Suggestions for respondents to know more about the benefits of posyandu for pregnant women are clearer than health workers.